Kinetic Modeling of the Monoamine Oxidase B Radioligand [11C]SL25.1188 in Human Brain with High-Resolution Positron Emission Tomography. Issue 5 (May 2014) - Rusjan, Pablo M; Wilson, Alan A; Miler, Laura; Fan, Ian; Mizrahi, Romina; Houle, Sylvain; Vasdev, Neil; Meyer, Jeffrey H
This article describes the kinetic modeling of [ 11 C]SL25.1188 ([(S)-5-methoxymethyl-3-[6-(4, 4, 4-trifluorobutoxy)-benzo[ d ]isoxazol-3-yl]-oxazolidin-2-[ 11 C]one]) binding to monoamine oxidase B (MAO-B) in the human brain using high-resolution positron emission tomography (PET). Seven healthy subjects underwent two separate 90-minute PET scans after an intravenous injection of [ 11 C]SL25.1188. Complementary arterial blood sampling was acquired. Radioactivity was quickly eliminated from plasma with 80% of parent compound remaining at 90 minutes. Metabolites were more polar than the parent compound. Time-activity curves showed high brain uptake, early peak and washout rate consistent with known regional MAO-B concentration. A two-tissue compartment model (2-TCM) provided better fits to the data than a 1-TCM. Measurement of total distribution volume ( V T ) showed very good identifiability (based on coefficient of variation (COV)) for all regions of interest (ROIs) (COV( V T )<8%), low between-subject variability (˜20%), and quick temporal convergence (within 5% of final value at 45 minutes). Logan graphical method produces very good estimation of V T . Regional V T highly correlated with previous postmortem report of MAO-B level ( r 2 = ≤0.9). Specific binding would account from 70% to 90% of V T . Hence, V T measurement of [ 11 C]SL25.1 1 88 PET is an excellent estimation of MAO-B concentration.